The influence of various concentrations of natural food on the development, fecundity and production of planktonic crustacean filtrators - Węgleńska, Teresa (Państwowe Wydawnictwo Naukowe, 1971)
The paper is a study of the dependence among the concentration of natural food and the development, growth end fecundity rates of planktonic crustacean filtrators (Daphnia cucullata, D. longispina. Diaphanosoma brachyurum, Chydorus sphaericus, Eudiaptomus graciloides) which dominate in the pelagial of Mikołajskie Lake. On the basis of the obtained data the production of zooplankton community in various thermal and trophic conditions was calculated. The obtained results allowed for a precise quantitative evidence of a limiting significance of food in various natural situations, and to show various intensities of this dependence for different species which feed on various kinds of food.
Pages 427-473 : illustrations ; 24 cm
Bibliographical references (pages 467-471)
Abstract in Polish
Keywords: crustaceans; food; development; fertility; Poland; Mikołajskie Lake; Crustacea